2017
DOI: 10.4045/tidsskr.16.0621
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotikabruk og infeksjoner i sykehjem

Abstract: Usage of antimicrobial agents Usage in animals Therapeutic usage of veterinary antimicrobial agents ………………………………………… Antimicrobial and coccidiostat feed additives ……………………………………….… ……. Usage in humans Overall antibiotic sales ……………………………………………………………………….. Antibiotic usage in primary care ……………………………………………………………… Antibiotic usage in hospitals …………………………………………………………………. National Action Plan against Antibiotic Resistance in Healthcare .………………………….. Antimycotic usage in Norway ………………………………………………………………..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…On the other hand, several infection surveillance registries report a trend of decreasing rates of surgical site infection (SSI) after THA, including both superficial and deep infections (Manniën et al 2008 , Choi et al 2016 , Sodhi et al 2019 ). This was also the finding of the Norwegian Institute of Public Health’s SSI surveillance registry (Berg et al 2019 ). The European Centre for Disease Prevention and Control (ECDC) reports a stable in-hospital incidence of SSI after total hip arthroplasty since 2011 (ECDC 2019 ), similar to what we found for that period.…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, several infection surveillance registries report a trend of decreasing rates of surgical site infection (SSI) after THA, including both superficial and deep infections (Manniën et al 2008 , Choi et al 2016 , Sodhi et al 2019 ). This was also the finding of the Norwegian Institute of Public Health’s SSI surveillance registry (Berg et al 2019 ). The European Centre for Disease Prevention and Control (ECDC) reports a stable in-hospital incidence of SSI after total hip arthroplasty since 2011 (ECDC 2019 ), similar to what we found for that period.…”
Section: Discussionsupporting
confidence: 76%
“…The Healthcare-Associated infections in Long-Term care facilities (HALT) project showed that, among the participating countries, Denmark had the highest antibiotic use for elderly residing in nursing homes (NHs) [2]. In Europe, urinary tract infection (UTI) is the most common reason for antibiotic prescribing in NH residents [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It More than 80 per cent of the residents have dementia and need full-time attention (NPH, 2018). Residents in nursing homes have a relatively low tolerance for acute infections (Kittang & Krüger, 2018) and have a higher risk of developing infections that require antibiotics treatment than do elderly people living at home (Alberg et al, 2017). Approximately 7.8% of the residents received antibiotics in 2016 (NPH, 2017).…”
Section: Introductionmentioning
confidence: 99%